More than objects: Robot performance in Japan's Bacarobo Theatre - Sone, Yuji (Studies in theatre and performance, 2010)
This article examines Bacarobo, a Japanese comedy contest for robots that are designed to perform and entertain the audience with laughter. In the theatre of Bacarobo, robots can be comedians because the theatrical space and dynamics of Bacarobo attribute a performance capacity to its robots that makes them much more than just objects in themselves. The robot competition unites strategies typical of the Japanese variety show context with effects creating a temporary, consensual reality to present robots as integral players in humorous situations. In this inclusive mise-en-scène, Bacarobo combines the concept of robot as a magical object with the transformative power of the clown to draw upon the Japanese idea of the robot's role in forging a technologically advanced future. The result is that the uncertain and indeterminate aspects of the robotic machines-machines otherwise without practical use and, therefore, important social referents-are turned into something acceptable and even endearing in the name of comedy. The Japanese robot comedy show provides useful material to consider recent thinking within theatre and performance studies on the subject-object relation and on the activation of theatrical space, audience and objects.